2023
DOI: 10.3390/ijms242316898
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Performances of Blood-Count-Derived Inflammatory Markers for Liver Fibrosis Severity in Psoriasis Vulgaris

Oana Mirela Tiucă,
Silviu Horia Morariu,
Claudia Raluca Mariean
et al.

Abstract: Psoriasis is an immune-mediated, chronic disorder that significantly alters patients’ quality of life and predisposes them to a higher risk of comorbidities, including liver fibrosis. Various non-invasive tests (NITs) have been validated to assess liver fibrosis severity, while blood-count-derived inflammatory markers have been proven to be reliable in reflecting inflammatory status in psoriatic disease. The fibrosis-4 (FIB-4) index became part of the newest guideline for monitoring psoriasis patients undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Additionally, these markers can be used as indicators of all-cause mortality [31] and cardiovascular disease [32]. We have recently shown their reliability in assessing liver fibrosis [33] in psoriasis. NLR and PLR decreased in a similar form to the C-reactive protein (CRP) in Japanese patients treated with all kinds of biologics [34], and can, therefore, be useful in assessing the response to systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these markers can be used as indicators of all-cause mortality [31] and cardiovascular disease [32]. We have recently shown their reliability in assessing liver fibrosis [33] in psoriasis. NLR and PLR decreased in a similar form to the C-reactive protein (CRP) in Japanese patients treated with all kinds of biologics [34], and can, therefore, be useful in assessing the response to systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified various blood-count-derived inflammatory markers to be associated with psoriasis. The most extensive studies, on neutrophil-to-lymphocyte ratio (NLR) and platelets-to-lymphocyte ratio (PLR), adequately reflect disease severity, treatment response [25], and various comorbidities associated with psoriasis, such as liver fibrosis [26], cardiovascular disease [27,28], or articular damage [29]. Even though several studies focusing on peripheral leucocytes and various subsets are available, as presented earlier, no published reports refer to eosinophil-count-derived inflammatory markers and psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the positive correlation of increased SII quartiles and Ln (SII) with the risk of MAFLD and SCAS persisted. Additionally, SII has been validated as a diagnostic index for various inflammatory digestive diseases ( 34 , 35 ) and coronary artery disease ( 36 ). Similarly, this study also found that SII exhibited a favorable diagnostic value for MAFLD and SCAS.…”
Section: Discussionmentioning
confidence: 99%